Collaborative leadership in team science: dynamics of sense making, decision making, and action taking - Jiang, Gemma (Frontiers in Research Metrics and Analytics, 2023)
To help cross-disciplinary science teams navigate through internal and external complexities, this perspective article explores the application of three conceptual frameworks: Theory U, Divergence-Convergence Diamond, and Strategic Doing. These frameworks enable science teams to avoid common pitfalls by operationalizing collaborative leadership as iterative cycles of distributed sense making, decision making and action taking. Implications for team science practices include facilitating the process, prototyping the future and applying dynamic roles and responsibilities.